2014
DOI: 10.1155/2014/962161
|View full text |Cite
|
Sign up to set email alerts
|

Development of Membraneless Sodium Perborate Fuel Cell for Media Flexible Power Generation

Abstract: This paper reports the media flexibility of membraneless sodium perborate fuel cell (MLSPBFC) using acid/alkaline bipolar electrolyte in which the anode is in acidic media while the cathode is in alkaline media, or vice versa. Investigation of the cell operation is conducted by using formic acid as a fuel and sodium perborate as an oxidant for the first time under "acid-alkaline media" configurations. The MLSPBFC architecture enables interchangeable operation with different media combinations. The experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The MLSPBFC can thus be run in a mixed-media configuration in which the anode can be alkaline while the cathode is acidic, or vice versa, to improve individual electrode kinetics and thermodynamics. The MLSPBFC operated in the alkaline anode/acidic cathode mixed-media configuration, a large OCP of 1.72 V was measured, which, in light of the known overpotentials at both the cathode and the anode, is in good agreement with the theoretical OCP of 2.95 V. These large potentials result in a rather unusual phenomenon for fuel cells; at high current densities, once the oxygen has been depleted from the oxidant stream, proton reduction becomes the cathode reaction [25,26]. Operating in this Alkaline-acid media configuration, with an alkaline anode and an acidic cathode, resulted in a higher overall cell potential than those obtained for the all acidic and all-alkaline MLSPBFC experiments.…”
Section: Hydrazine / Perborate In Acidic Mediumsupporting
confidence: 73%
“…The MLSPBFC can thus be run in a mixed-media configuration in which the anode can be alkaline while the cathode is acidic, or vice versa, to improve individual electrode kinetics and thermodynamics. The MLSPBFC operated in the alkaline anode/acidic cathode mixed-media configuration, a large OCP of 1.72 V was measured, which, in light of the known overpotentials at both the cathode and the anode, is in good agreement with the theoretical OCP of 2.95 V. These large potentials result in a rather unusual phenomenon for fuel cells; at high current densities, once the oxygen has been depleted from the oxidant stream, proton reduction becomes the cathode reaction [25,26]. Operating in this Alkaline-acid media configuration, with an alkaline anode and an acidic cathode, resulted in a higher overall cell potential than those obtained for the all acidic and all-alkaline MLSPBFC experiments.…”
Section: Hydrazine / Perborate In Acidic Mediumsupporting
confidence: 73%
“…The best performance observed for these electrocatalysts could be explained by a bifunctional mechanism and ligand (electronic) effect, as well assumed for various Pt-based electrocatalysts. [21][22][23][24][25] As mentioned in our earlier studies, 5,6 the effects of perborate concentration on the cell performance were investigated at different concentrations and the power density increased as sodium perborate concentration increases in the membraneless fuel cell system. The results demonstrated that the performance of the developed membraneless fuel cell enhanced profoundly if the concentration of oxidant in cathodic stream is 10 times larger, and the current density is also increased approximately ten times.…”
Section: Single Cell Performancementioning
confidence: 97%
“…It is a peroxo salt with anionic formula B 2 (O 2 ) 2 (OH) 4 2À . Perborate is a convenient source of H 2 O 2 , [6][7][8][9][10][11][12] commercially, industrially and also in the laboratory as demonstrated in eqn (1).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 18 ] reported CFD analysis on the performance of membrane-less hydrogen peroxide fuel cell system that operated in dual-electrolyte media and found that the geometric design of the electrode is vital for the performance. In another study, Ponmani et al [ 19 ] developed a membrane-less sodium perborate fuel cell (MLSPBFC) in dual-electrolyte medium, which resulted in a high OCV for the combination of alkaline at the anode and acidic at the cathode side.…”
Section: Introductionmentioning
confidence: 99%